ANALISIS KARAKTERISTIK MASYARAKAT SUBANG DAN KEPUTUSAN DIVERSIFIKASI INVESTASI - Estu Widarwati; Pupung Purnamasari; Annisa Herdianti; Rina Yuni Astuti; Rispa Siti Nurhasanah (JABI (Journal of Accounting and Business Issues), 2024)
The rate of economic growth in Subang district in 2021 according to the Central Statistics Agency for Subang district during the period 2017-2021 fluctuated growth rate. In today's economic times, most are aware of the importance of investing. Many people have started to invest both in the capital market and in assets such as land, property or in the form of businesses. The purpose of this study is to find out how the characteristics of the Subang community are, to find out how to diversify the Subang community. To determine the effect of characteristics on investment diversification, this study uses a descriptive verification method with a quantitative approach. Data collection techniques used questionnaires, literature studies and observations using 100 respondents from the Subang district community which was carried out on June 9, 2022. The results of this study were that gender had no effect on investment diversification decisions, age had no effect on investment diversification decisions, and education had no effect on investment diversification decisions. on investment diversification decisions, occupation does not affect investment diversification decisions, and income affects investment diversification decisions, thus the characteristics of the people of Subang Regency have no effect on investment diversification decisions in Subang Regency. Most respondents are female, the age of most respondents is in the range of 17-25 years. The income of most respondents is in the range of 1-3 million. The education of most respondents is SMA/SMK. Most of the respondents' occupations are entrepreneurs. Most of the respondents live in Subang.